SCIPA Full-On: A Randomized Controlled Trial Comparing Intensive Whole-Body Exercise and Upper Body Exercise After Spinal Cord Injury. (June 2018) - Galea, Mary P.; Dunlop, Sarah A.; Geraghty, Timothy; Davis, Glen M.; Nunn, Andrew; Olenko, Liudmyla
Background . While upper body training has been effective for improving aerobic fitness and muscle strength after spinal cord injury (SCI), activity-based therapies intended to activate the paralyzed extremities have been reported to promote neurological improvement. Objective . To compare the effectiveness of intensive whole-body exercise compared with upper body exercise for people with chronic SCI. Methods . A parallel-group randomized controlled trial was conducted. Participants with a range of SCI levels and severity were randomized to either full-body exercise (FBE) or upper body exercise (UBE) groups (3 sessions per week over 12 weeks). FBE participants underwent locomotor training, functional electrical stimulation-assisted leg cycling, and trunk and lower extremity exercises, while UBE participants undertook upper body strength and aerobic fitness training only. The primary outcome measure was the American Spinal Injury Association (ASIA) motor score for upper and lower extremities. Adverse events were systematically recorded. Results . A total of 116 participants were enrolled and included in the primary analysis. The adjusted mean between-group difference was −0.04 (95% CI −1.12 to 1.04) for upper extremity motor scores, and 0.90 (95% CI −0.48 to 2.27) for lower extremity motor scores. There were 15 serious adverse events in UBE and 16 in FBE, but only one of these was definitely related to the experimental intervention (bilateral femoral condyle and tibial plateau subchondral fractures). No significant between-group difference was found for adverse events, or functional or behavioral variables. Conclusions . Full-body training did not lead to improved ASIA motor scores compared with upper body training in people with chronic SCI.